Awareness of Diabetes Mellitus among Uae Non-Diabetic Population in Ajman and Ras Alkhaimah - Nehad M. Hamoudi, Istabraq Dhia Al Ayoubi, Shatha Al Sharbatti, A. A. Shirwaikar (Journal of Applied Pharmaceutical Science)
The present study aims to assess the level of knowledge of DM among non diabetic people from Ajman and Ras Al Khaimah (UAE) regard to causes, complication, clinical manifestation, management, treatment, drug adherence and control, hypoglycemia associated with diabetic therapy, hypoglycemia management and other aspects related to diabetes. A cross-sectional study was conducted among non diabetic people who were attending GMCH (Gulf Medical College Hospital) community pharmacy in Ajman and RAK hospitals during the period between July and December 2009. A self-administered questionnaire was used as a tool for data collection. The percentage of participants aware of diabetes causes, symptoms, complications, management, drug treatment, drug therapy adherence and diabetes monitoring were 60.4%, 78.7%, 54.8%, 68.9%, 89.8%, 50.6%, and 76.6% respectively. Awareness of hypoglycemic symptoms which can complicate diabetes therapy was only low 23.8%. For the management of hypoglycemia 45.1% of the participants recommended the use of sugar, 23% of them suggested the use of oral medicine and 32% of the participants recommended the use of insulin. The proportions of participants who had correct knowledge of the recommended frequency of follow-up of eye exam, urine test, blood sugar measurement and blood pressure test in diabetic patients were 33.6%, 39.6%, 87.2% and 23.8 respectively. The study showed low awareness of the population about various aspects of diabetes and the least knowledge was noticed on hypoglycemic symptoms, hypoglycemia management and diabetes complications. We recommend education program to improve population knowledge regards diabetes which can create enthusiasm to improve diabetes care and can go a long way in the prevention and management of diabetes in the Gulf region and UAE in particular.
Keywords: Diabetes Mellitus, People awareness, Hypoglycemia management, Knowledge.